Materiality in Roman Art and Architecture : Aesthetics, Semantics and Function. - Haug, Annette. (Decorative Principles in Late Republican and Early Imperial Italy (Decor) Series, 2022)
DECOR is the first series that considers decorative phenomena in a comprehensive way. It moves away from the study of single decorative elements in isolation, focusing instead upon their spatial-architectural and visual integration. This serves as the starting point for a differentiated analysis of image- or decor-spaces. The geographical focus is on Italy, the chronological framework ranges from the 2ndcentury B.C. to the late 1st century A.D.